AN OVERLOOKED POTENTIAL OF A FANTASY FILM TO HONE CRITICAL GENDER LITERACY - Nurhadianty Rahayu; Siti Habsah; Deddy Suprapto (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2023)
This study attempts to explore the potentiality of a fantasy film, i.e., Maleficent, to be used as a tool to sharpen language learners’ critical literacy toward the issue of gender construction. The purpose of the study is to unravel the genre of fantasy film as a space to deconstruct the way gender is represented. This study borrows the framework of postcolonial feminism in deconstructing and reconstructing the portrayal of the main female protagonist. As the study also discusses the insights of using film as a tool to facilitate language learning, the data is also gained from the teacher-student written and verbal reflection. The reflection data is then analyzed using narrative analysis proposed by (Creswell, 2012). The study gives insights into how fantasy films can be used for language teaching. The analysis of Maleficent as a powerful tool to sharpen language learners’ critical gender literacy.